Voices of change in the Global South: Understanding the dynamics of environmental protest - Rebecca Strauch; Viktoria Jansesberger; Sebastian Koos; Gabriele Spilker (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
Environmental degradation, ranging from air and water pollution to land degradation and climate change, often generates discontent and grievances among affected populations. Such dissatisfaction with living conditions can foster political unrest, as individuals may protest publicly to voice their concerns and demand action from authorities. In light of increasing climate change and its widespread impacts, scholars have questioned whether environmental changes could become a destabilizing factor, promoting overall levels of unrest. To address this issue, several related questions concerning the nature of environmental mobilization must be explored: Have environmental issues become more prominent in protests? If so, which specific issues are mentioned and in which regions are they most vocalized? Additionally, are environmental protests systematically different from other forms of political protest, perhaps by attracting more participants or more frequently involving violent tactics? To better understand the origins and dynamics of environmental mobilization, we present a new dataset covering environmental protests in the Global South. This region, despite its low historical emissions, is particularly affected by environmental issues linked to climate change. Our dataset geo-codes environmental dissent at both national and local levels, identifies actors and political demands, and collects information on violence and repression. This new data enhances the scope of existing research and provides a robust foundation to address the research questions introduced.
urn:nbn:de:bsz:352-2-1ween35c8fd7z6
Keywords: 320; Environmental degradation; climate change; protest; mobilization